Gastric gland mucin‐specific O‐glycan expression decreases with tumor progression from precursor lesions to pancreatic cancer. Issue 9 (8th August 2017) - Ohya, Ayumi; Yamanoi, Kazuhiro; Shimojo, Hisashi; Fujii, Chifumi; Nakayama, Jun
Abstract : Pancreatic cancer is lethal, as it is often detected late. Thus, novel biomarkers of precursor lesions are needed to devise timely therapies. Pancreatic intraepithelial neoplasia (PanIN) and intraductal papillary mucinous neoplasm (IPMN) are major precursors of pancreatic cancer. In normal gastric mucosa, gastric gland mucin‐specific O ‐glycans are unique in having α1, 4‐linked N ‐acetylglucosamine (αGlcNAc) residues attached to MUC6. Recently we reported that αGlcNAc functions as a tumor suppressor for differentiated‐type gastric adenocarcinoma (Karasawa et al ., J Clin Invest 122, 923, 2012). MUC6 is also expressed in pancreatic neoplasms, including PanIN and IPMN, but the role of αGlcNAc expression in pancreatic neoplasms remains unknown. Here, we analyze expression patterns of αGlcNAc, MUC6 and MUC5AC in pancreatic neoplasms and compare them with progression from PanIN to invasive ductal adenocarcinoma (IDAC) (the PanIN‐IDAC sequence; 20 cases) and from IPMN to IPMN with associated invasive carcinoma (IPMNAIC) (the IPMN‐IPMNAIC sequence; 20 cases). At both sequences, the frequency of MUC6‐positive and αGlcNAc‐positive lesions decreased with tumor progression. We then compared expression levels of αGlcNAc and MUC6 at each step of the progression. At the PanIN‐IDAC sequence, αGlcNAc expression significantly decreased relative to MUC6 in low‐grade PanIN ( P = 0.021), high‐grade PanIN/intraductal spread of IDAC ( P = 0.031) and IDAC ( P = 0.013). At the IPMN‐IPMNAIC sequence, decreased αGlcNAc expression was also observed in low‐grade IPMN exhibiting gastric‐type morphology ( P = 0.020). These results suggest that decreased expression of αGlcNAc relative to MUC6 occurs early and marks the initiation of tumor progression to pancreatic cancer. Abstract : Gastric gland mucin‐specific O ‐glycans, αGlcNAc attach to MUC6 as a scaffold, and function as a tumor suppressor for gastric cancer. In the present study, we demonstrated that expression level of αGlcNAc relative to MUC6 begins to decrease early in pancreatic tumor progression from precursor lesions including PanIN and IPMN to invasive ductal carcinoma. Thus, decreased αGlcNAc expression occurs early and marks the initiation of tumor progression to pancreatic cancer.